1982
DOI: 10.1161/01.cir.66.3.496
|View full text |Cite
|
Sign up to set email alerts
|

The QT interval throughout the first 6 months of life: a prospective study.

Abstract: A prospective electrocardiographic study was designed to establish baseline values for electrocardiographic measurements, with specific reference to the QT interval during infancy, and to test the "QT hypothesis" for the sudden infant death syndrome (SIDS). In this ongoing study, ECGs are recorded on the fourth day of life and in the second, fourth and sixth months. The state of health at 1 year is ascertained by a phone call. So far, 4205 newborns have been enrolled. The mean QTc (QT interval corrected for he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
2
4

Year Published

1985
1985
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(73 citation statements)
references
References 36 publications
7
60
2
4
Order By: Relevance
“…The corresponding 98th percentile QTc values for the cisapride treated groups were: 504 ms; 458 ms; and 451 ms, respectively. Thirty of the 64 group 1 cisapride patients (46.9%) had a QTc Bazett's formula value beyond 455 ms. 11 Of these 30 infants, 2 had a QTc value Ͼ480 ms and in another 2 infants the QTc value was Ͼ500 ms (505 ms and 507 ms). Two of the group 2 cisapride patients had a QTc Bazett's formula value above 455 ms (457 ms in both) and none in the cisapride group 3 patients.…”
Section: Resultsmentioning
confidence: 98%
“…The corresponding 98th percentile QTc values for the cisapride treated groups were: 504 ms; 458 ms; and 451 ms, respectively. Thirty of the 64 group 1 cisapride patients (46.9%) had a QTc Bazett's formula value beyond 455 ms. 11 Of these 30 infants, 2 had a QTc value Ͼ480 ms and in another 2 infants the QTc value was Ͼ500 ms (505 ms and 507 ms). Two of the group 2 cisapride patients had a QTc Bazett's formula value above 455 ms (457 ms in both) and none in the cisapride group 3 patients.…”
Section: Resultsmentioning
confidence: 98%
“…9 Manoach et al showed that the ECG of newborn mice with a prolonged QT interval is similar to that of mouse embryos in the intermediate stage, while the ECG in normal newborns resembles that of the prenatal fetus. 10 Fein et al demonstrated a good correlation between the number of undifferentiated myoblasts in the ventricular walls and typical prolongation of the QT interval in rats and mice.…”
Section: Discussionmentioning
confidence: 99%
“…10 Studies of infants in Italy and a recent study of infants in Japan have shown that QTc intervals were longest at ≈2 months of age. 11,12 A large study conducted in Italy showed that the prevalence of LQTS might be close to 1:2000 13 ; however, no studies have been conducted outside Europe. In Japan, medical examinations during infancy are mandatory, and medical examinations at 1 month of age are currently performed on all infants.…”
Section: Clinical Perspective On P 938mentioning
confidence: 99%